Comparison of inverted flap and subretinal aspiration technique in full-thickness macular hole surgery: a randomized controlled study. Issue 3 (May 2018) - Iovino, Claudio; Caminiti, Giulia; Miccoli, Mario; Nasini, Francesco; Casini, Giamberto; Peiretti, Enrico
Purpose: To compare the inverted flap and the subretinal aspiration technique for full-thickness macular hole (FTMH) surgery. Methods: Forty consecutive eyes with a stage IV FTMH were randomly assigned into 2 treatment groups. After core vitrectomy and perimacular internal limiting membrane (ILM) peeling, in group A, the subretinal remnant macular fluid was aspirated with a 41-G cannula after the air-fluid exchange procedure, while in group B, the technique of an inverted ILM flap was completed. Differences in postoperative best-corrected visual acuity (BCVA) and occurrence of intraoperative or postoperative complications between the 2 groups were evaluated. Results: All FTMHs were closed after the first surgery with no intraoperative or postoperative complications. In group A, 16 patients (80%) showed improvement of BCVA and 4 (20%) showed stabilization. In group B, 12 patients (60%) had improved BCVA, while 6 (30%) remained stable and 2 (10%) worsened. Postoperative BCVA for group A was significantly better than for group B (p = 0.022). Conclusions: The surgical techniques had similar rates of closure of FTMH, although BCVA outcomes were significantly better in the subretinal aspiration group.